Origin of red clays around Miskolc (North Hungary) - Vincze László (Acta mineralogica-petrographica, 2005)
During the geological mapping of the northern foreland of the Biikk Mountains red clay occurrences were identified by the Department of Mineralogy and Geology, University of Debrecen. Red clays are underlain by Triassic limestone and Miocene, mainly Sarmatian siliciclastic sediments containing tuffaceous bentonites. Based on the sedimentological (grain-size distribution), mineralogical (micromineralogy, X-ray diffraction, thermal analysis) and major element geochemical (ICP-OES) examinations, it can be established that the studied red clays belong to the less weathered, so-called „reddish clay" type. Montmorillonite prevails among clay minerals, while kaolinite is subordinate. Considering the strong sedimentological and mineralogical similarity with the underlying Miocene sediments, the red clays were probably originated by the weathering of the Miocene sediments under a moderately warm and dry climate. Taking lithostratigraphic features into account, the examined red clays can be classified as members of the Pliocene-Pleistocene Tengelic or Kerecsend Red Clay Formation.